2019
DOI: 10.1002/kjm2.12048
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of phosphodiesterase type 5 inhibitors for the treatment of distal ureteral calculi of 5 to 10 mm in size: A systematic review and network meta‐analysis

Abstract: To evaluate the Efficacy and safety of phosphodiesterase type 5 inhibitors as a medical therapy for distal ureteral calculi by means of a systematic review and network meta‐analysis (NMA). We searched the Embase, Medline, and the Cochrane Central Register of Controlled Trials for randomised controlled trials (RCTs) published before May, 2017. Stone passage rate as the primary outcome. We used random effects model for pairwise meta‐analyses and Bayesian random effects model for NMA. We evaluated the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Even meta-analyzes have reported conflicting results. While a meta-analysis by Li et al (24) showed that the time to expel stones in tadalafil group was significantly less than tamsulosin group (p=0.028), another meta-analysis by Liu et al, (25) in the same year reported no significant shorter stone expulsion time for tadalafil in comparison with tamsulosin.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Even meta-analyzes have reported conflicting results. While a meta-analysis by Li et al (24) showed that the time to expel stones in tadalafil group was significantly less than tamsulosin group (p=0.028), another meta-analysis by Liu et al, (25) in the same year reported no significant shorter stone expulsion time for tadalafil in comparison with tamsulosin.…”
Section: Discussionmentioning
confidence: 95%
“…Liu et al (25), in their meta-analysis, showed that using tadalafil is associated with more side effects such as headache, dizziness, backache, and orthostatic hypotension than tamsulosin. But another meta-analysis by Li et al (24), reported no statistic difference between tamsulosin group and tamsulosin plus tadalafil group in terms of drug's adverse effects (p >0.05).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations